Carbon Dioxide Emissions Inventory with GIS - Hamal, Kh.V. (Інститут проблем штучного інтелекту МОН України та НАН України, 2008)
The paper emphasizes the need of spatially distributed carbon dioxide (CO2) inventory using geoinformation system. It describes the available activity data on fuel combustion in Ukrainian statistics and proposes algorithms for their territorial distribution. The information system for spatial inventory is described and an example of its application for one of Ukrainian administrative regions is presented.